MIDDLE TRIASSIC SPIRIFEROID MENTZELIIDS (BRACHIOPODA) FROM ALPINE AND MEDITERRANEAN AREAS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2015)
Ten species of mentzelioid spiriferids from several Middle Triassic localities of Alpine and Mediterranean areas are analysed both for external and internal characters. The genera Mentzelia, Paramentzelia, Koeveskallina, and the new genus Dagyssia are referred to the subfamily Mentzeliinae, whilst Tethyspira and the new genus Ptychomentzelia are referred to the subfamily Tethyspirinae. In addition, a new species (Ptychomentzelia ritensis) is described. The superfamily Mentzelioidea Dagys, 1974 is retained as a viable container of the whole group here discussed, previously split in the second edition of the Treatise in two different superfamilies.
Keywords: Brachiopods; mentzeliids; taxonomy; Middle Triassic; internal characters